Analysis of Personnel in the Field of Taxation by the Minister of Finance through the Tax Supervisory Committee - Cahyady, Yadhy; Trisulo, Trisulo (Dinasti International Journal of Economics, Finance & Accounting, 2026)
The Ministry of Finance as one of the State Ministries is responsible for managing government affairs in the financial sector. It operates under the authority of and is accountable to the President, with leadership vested in the Minister of Finance. In executing its responsibilities, the Ministry of Finance performs various functions, including the formulation, determination, and implementation of taxation policies. This study aims to examine the position and authority of the Minister of Finance in overseeing taxation matters through the Tax Supervisory Committee. The research employs a normative legal approach, utilizing both statutory and conceptual analyses, with secondary sources such as laws and reference literature obtained through document and library studies. The findings indicate that the Minister of Finance, as the head of the Ministry and superior to the Director General of Taxes, holds supervisory authority over subordinates, including the Director General. Supervision conducted via the Tax Supervisory Committee focuses on tax policies and administration, but does not extend to overseeing the resolution of tax disputes through administrative measures determined by the Director General of Taxes.